Dampak Program Kampung Pelangi Terhadap Status Cemar Sungai Kemuning Berdasarkan Parameter Limbah Domestik - Ahmad Ridwan Rosyadi; Emmy Sri Mahreda (EnviroScienteae, 2021)
The objectives of this study were to: 1) analyze the water quality of Kemuning River after Kampung Pelangi program based on water quality standard class 2, 2) analyze the polluted status of the Kemuning River based on class II water quality standard before and after Kampung Pelangi program, 3) analyze the polluted status per parameter from the upstream, downstream and middle of the Kemuning River based on domestic waste parameter. This study was conducted in Kemuning River, Banjarbaru City, South Kalimantan. Measurement and sampling of the water was carried out through direct observation and measurement in the field (in situ) and laboratory testing (ex situ). Sampling locations included the upstream river, the middle part that passed through Kampung Pelangi, and the downstream/ estuary section. The results of this study found that the water quality after Kampung Pelangi program was not polluted in the upstream with a PI value of 0.2629, was mildly polluted in the middle and downstream with PI values of 3.258 and 3.152. The polluted status improved after Kampung Pelangi program in 2017 - 2018 compared to 2016. However, it experienced an increase in 2019. The polluted status exceeded class II water quality standards in the parameters of COD, BOD, and Phosphate due to domestic waste such as rubbish, industrial waste tempeh, and detergent from the laundry business.